Gastroesophageal reflux and chest physiotherapy: review - Gonçalves, Renata M.; Assumpção, Maíra S. de; Schivinski, Camila I. S. (Medicina (Ribeirao Preto), 2015)
Objective: to present scientific evidence on the impact of respiratory physiotherapy techniques (RPT) in episodes of gastroesophageal reflux (GER) and gastroesophageal reflux disease (GERD) in pediatric population, as well as characteristics of the studied samples, evaluation tools, RPT applied and the results obtained. Method: Systematic review operationalized through electronic search of three databases: LILACS, MEDLINE and Science Direct, in the period February to April 2014, using the keywords: gastroesophageal reflux, gastro-oesophageal reflux, physiotherapy / physical therapy, respiratory / chest. Studies evaluating the effects of RPT (conventional and modern) in children with GER and / or diagnosed with GERD were selected. Results: 73 articles were identified on the subject, and a sequential process excluded those who did not meet the inclusion criteria previously established. At the end of the calculation we included eight articles, seven clinical trials and one report series of cases. There was a higher frequency in the assessment of the impact on the conventional RPT about GER in children with cystic fibrosis, and postural drainage, associated or not with other techniques, applied in most studies, however, the effects of the described RPT may be still controversial. More recent studies have analyzed other RPT (increased expiratory flow handlings and method thoracoabdominal rebalancing) verifying their capability of causing reflux and security in the application of handlings. Conclusions: there is lack of research on the subject, there is no consensus as to the effect of RPT on GER in the pediatric population, especially in children with cystic fibrosis. In these investigations it was found that most of the examination of images used for the identification of GER.